Factors influencing interest in saving at Islamic bank: A study on the merchants of Pasar Besar in Malang City - Rahmawati, Laila; Rahayu, Yayuk Sri (Universitas Islam Indonesia, 2024)
IntroductionThe development of Islamic banks in Indonesia is pivotal for the growth of the Islamic economy, given the country's majority Muslim population. However, the adoption rate of Islamic banking services remains relatively low compared to the overall Muslim population, highlighting the need to understand the factors influencing customer interest in saving with Islamic banks.ObjectivesThis study aims to examine the impact of Sharia labels, product knowledge, and location on the interest in saving among merchants in Pasar Besar, Malang. Specifically, it seeks to determine how these factors individually and collectively influence customers' decisions to save in Islamic banks.MethodA quantitative research approach was employed, utilizing non-probability purposive sampling to gather data from 135 respondents through questionnaires. The analysis was conducted using IBM SPSS to perform validity, reliability, normality, heteroscedasticity, multicollinearity, and multiple linear regression tests to validate the hypotheses.ResultsThe findings indicate that Sharia labels, product knowledge, and location significantly affect the interest in saving. Specifically, the t-test results show that each variable has a statistically significant impact, with t-values greater than the t-table value of 1.978. Additionally, the F-test confirms that these variables collectively influence the interest in saving, with an F-value of 50.579 exceeding the threshold of 2.67.ImplicationsThe study's implications for further research suggest exploring additional factors such as customer service quality and financial incentives, and employing mixed-method approaches to gain deeper insights. For policymakers and Islamic banks, the findings highlight the importance of enhancing Sharia compliance visibility, improving customer education on Islamic banking products, and strategically locating bank branches to attract more customers.Originality/NoveltyThis study offers a novel exploration of the combined effects of Sharia labels, product knowledge, and location on saving interest in the context of Islamic banking. It provides new insights into customer behavior in a specific market segment, contributing to the broader understanding of factors that influence the adoption of Islamic financial services.